2012
DOI: 10.1111/j.1365-2966.2012.20757.x
|View full text |Cite
|
Sign up to set email alerts
|

2008 LC18: a potentially unstable Neptune Trojan

Abstract: The recent discovery of the first Neptune Trojan at the planet's trailing (L5) Lagrange point, 2008 LC18, offers an opportunity to confirm the formation mechanism of a member of this important tracer population for the Solar system's dynamical history. We tested the stability of 2008 LC18's orbit through a detailed dynamical study, using test particles spread across the orbital uncertainties in a, e, i and {\Omega}. This showed that the wide uncertainties of the published orbit span regions of both extreme dyn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 44 publications
2
29
2
Order By: Relevance
“…Instead, they must be continually replenished. Over the years, a number of other solar system small body populations have been suggested as potential sources for the Centaurs, including captured Oort Cloud comets (e.g., Emel'yanenko et al 2005;Brasser et al 2012;Fouchard et al 2014), the Jovian Trojans (e.g., Horner & Evans 2006;Horner et al 2012b), and the Neptune Trojans (Horner & Lykawka 2010a, 2010bHorner et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they must be continually replenished. Over the years, a number of other solar system small body populations have been suggested as potential sources for the Centaurs, including captured Oort Cloud comets (e.g., Emel'yanenko et al 2005;Brasser et al 2012;Fouchard et al 2014), the Jovian Trojans (e.g., Horner & Evans 2006;Horner et al 2012b), and the Neptune Trojans (Horner & Lykawka 2010a, 2010bHorner et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…The Minor Planet Center (MPC) lists nine Neptune Trojans (six L4, three L5), but one of the L5 Trojans is unstable and likely a recently captured Centaur (Gladman et al 2012, Horner et al 2012). This object is therefore not considered to be reflective of the intrinsic inclination distribution of the (putatively primordial) Neptune Trojans.…”
Section: Samplementioning
confidence: 99%
“…In our studies of the other potentially unstable Neptune Trojans 2001 QR 322 (Horner & Lykawka ) and 2008 LC 18 (Horner et al ), we found that their stability was a strong function of their initial orbital parameters, and that both objects had orbital uncertainties that spanned regions of both great dynamical stability and significant dynamical instability. As such, it is clearly interesting to consider whether the stability of 2004 KV 18 is similarly influenced by the choice of initial orbital elements used.…”
Section: Resultsmentioning
confidence: 56%
“…Such a range of capture outcomes is clearly seen in theoretical work modelling the origin of both the Neptunian and Jovian Trojan populations (e.g. Morbidelli et al ; Lykawka et al , ; Lykawka & Horner ), and so it is unsurprising that recent dynamical studies have revealed that both 2001 QR 322 and 2008 LC 18 might be such dynamically unstable Neptunian Trojans (Horner & Lykawka , ; Horner et al ). Indeed, recent work has revealed that one of the Jovian Trojans, (1173) Anchises, is definitively dynamically unstable (Horner, Müller & Lykawka ) – adding further weight to the capture hypothesis.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation